The Hydrodynamic Tail Vein Assay as a Tool for the Study of Liver Promoters and Enhancers - Kim, Mee J. (2013)
The hydrodynamic tail vein injection is a technique that is used to deliver nucleic acids into live mice. Delivery through this method results in the in vivo transfection of foreign DNA primarily in the liver. Here, we describe the use of this technique to test for regulatory activity of liver promoters and enhancers, using a dual luciferase reporter system as the readable/measureable output and how this application can be used for pharmacogenomic studies.